Obese trauma patients who sustain orthopaedic fractures experience increased length of stay, ICU admissions and mortality - Brendan R Southam; Katherine A Bowers; Kevin P Smidt; Jane C Khoury; Mekibib Altaye; Michael T Archdeacon; Frank R Avilucea (Open Journal of Trauma - Peertechz Publications, 2020)
The rising trend of obesity in the United States has been a growing concern within the healthcare system for decades. Since the early 1960s, the prevalence of obesity has more than doubled among U.S. adults, and one out of every three Americans is now considered obese according to the National Health and Nutrition Examination Survey [1,2]. Significant medical comorbidities have been associated with obesity and increased Body Mass Index (BMI); these include hypertension, dyslipidemia, coronary artery disease, stroke, sleep apnea, type II diabetes mellitus and certain types of cancer.